Constraints and Determinants in the Adoption of Mechanisation in Rice Cultivation - Regina, F. Mary; James, P. Shaji; Ahamed, P (Journal of Agricultural Extension Management, 2019)
In an effort to sustain rice cultivation in Kerala, there has been a major thruston farm mechanisation by the State as well as the local self governmentsespecially in Palakkad and Thrissur districts of Kerala. This study was taken up toidentify the major constraints and determinants in the adoption of mechanisationin rice cultivation. Socio-economic constraints include small holding size, lackof unity among the farmers to adopt group mechanization followed by thetechnological constraint i.e, non-availability of skilled personnel for operation.Important determinants in the adoption of rice mechanization includeavailability of machines, availability of trained operators, initiative andresponsibility in upkeep of machinery and the unity of farmers. There is a needfor awareness programs apart from focus on a group mechanisation strategywhere individual holdings are too small to own machines.